Statistical hypothesis testing with SAS and R - Taeger, Dirk (Wiley, 2014)
"This book provides a reference guide to statistical tests and their application to data using SAS and R.A general summary of statistical test theory is presented, along with a general description for each test, together with necessary prerequisites, assumptions, and the formal test problem. The test statistic is stated together with annotations on its distribution, along with examples in both SAS and R. Each example contains the code to perform the test, the output, and remarks that explain necessary program parameters"--